NEGATIVE IMPACT AND EFFORTS TO RESPOND TO TOURISM DEVELOPMENT IN INDONESIA, ESPECIALLY IN BINTAN ISLAND, RIAU ISLANDS PROVINCE - Brian Kawasi; Sri Rahima; Dwi Junila Sari; Aprianingsih; Fadliyah Anas Tjatoer; Nike Astarina; Indrayani; Muammar Khaddafi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
From the above evidence in carrying out development, it can be concluded that Indonesian tourism in general and Bintan Island in particular has experienced There are indications of an imbalance of power relations between the countries of origin of tourists (developed countries) and developing countries as hosts. Tourist dissatisfaction is often seen as the fault of the host country. Like a new model of Imperialism (John A Hobson's Theory of Addiction). The imbalance in the inflow of various multinational companies into the development of Indonesia's tourism sector is flowing so swiftly. There are too many foreign investors so that Indonesia has been flooded with various international star hotel chains, from Jakarta to Irian Jaya. Meanwhile, national products have weak competitiveness. do not have high bargaining power, even in the domestic market causing a new model of Imperialism (John A Hobson's Dependency theory). The occurrence of damage to the environment and traditional culture. The relationship between hosts and tourists as guests, is more like slaves with their masters. The host, due to economic considerations, sacrifices everything for the satisfaction of his guests. (Theory of Sustainable Development). There are indications that tourism is a new/covert form of imperialism, there is dependence on the receiving country/region to comply with the wishes of tourists because they want to reach the international market/for economic benefits. Meanwhile, the host country is unable to compete in entering the international market mechanism. Governments and business people in countries/regions receiving tourists are subject to the interests of tourists, for the sake of foreign exchange. Various policies in the field of tourism and tourism products are designed to set aside people's rights.